Enhancing workplace conflict resolution in Malaysia: Lessons from Japan’s consensus-building practice of nemawashi in industrial relations - Ismail , Fadillah (Journal of Islamic, Social, Economics and Development, 2025)
This study examines the conflict-mitigating potential of ‘Nemawashi’, a Japanese consensus-building practice, in Malaysian workplaces. In Malaysia, conflict often results from gaps in communication and misaligned goals between employees and management, which affects the company's performance. ‘Nemawashi’ advocates informal dialogues in advance and can be applied during scenarios like negotiating workplace policies or arising disputes over job assignments to gain consensus on both parties of a dispute. By building common understanding and securing agreement up front, this practice aligns with the cultural values of harmony and fulfils statutory obligations, namely Sections 18 and 20 of the Industrial Relations Act 1967. However, it may face resistance to change since each workplace has different dynamics and consensus-building calls for training. Recommendations include embedding ‘Nemawashi’ in company policies, holding consensus-building skills development workshops, and establishing open communication channels. This strategy fosters a collaborative Nemawashi’, Workplace Conflict and Industrial Relationsand proactive working environment, benefiting Industrial Relations in Malaysia.